Development of an Arduino Nano-Based Viscometer to Enhance Students' Physics Concept Understanding - Saputra, Holis Angga; Gunada, I Wayan; Wahyudi, Wahyudi (Department of Physics Education, Universitas Mataram, 2025)
The understanding of the physics concept of viscosity is often hindered by its abstract nature and the limited availability of experimental tools in schools, leading to theoretical and suboptimal learning. Therefore, an innovative learning package needs to be developed to address these issues. This study aimed to develop this learning package and to test whether the resulting product is valid, practical, and effective for enhancing student's conceptual understanding. This study is a research and development adapting the procedural framework of the ADDIE model. The process involved 11th-grade SAINTEK students at SMAN 11 Mataram as trial subjects, with feasibility data collected through expert validation sheets, response questionnaires, and pretest-posttest questions for quantitative analysis. The data analysis indicated that the developed learning package consisting of an Arduino Nano-based viscometer, a teaching module, a student worksheet, and a test instrument achieved a very valid rating (average >89%), a very practical rating (92.00%), and was sufficiently effective with an average N-Gain score of 0.51 (medium category). Based on these results, it is concluded that the developed learning package is valid, practical, and sufficiently effective to be used for enhancing students' understanding of physics concepts.